Social, Political, and Phisolophical Aspects of the Education of Talented Children - Segura Chanto, Shirley (2012)
Talent is a topic that most people think they know, stimulate and deal with, but the truth is that few people can identify real talent. In Cost Rica, there are talented children that are not noticed, sometimes by their own parents and even by teachers, with little help to identify it and a treatment that does not fulfill their basic needs. They have the same rights and deserve an education according to their needs, in which their talents can be stimulated without their being confused with gifted children. At school, children do not have enough tools because teachers do not have the knowledge or training to identify them and provide the stimulation for their talent for them not only to highlight but also to adjust the programs to their needs. This is unfortunate, and it will be described later that this is a constant situation in this country. In the following essay, three perspectives around this topic will be described, and the ideas mentioned before will be elaborated on.